2021
DOI: 10.26434/chemrxiv.13708570.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Origin of Enhanced Water Oxidation Activity in an Iridium Single Atom Catalyst

Abstract: <p>The efficiency of the synthesis of renewable fuels and feedstocks from electrical sources is limited at present by the sluggish water oxidation reaction. Single atom catalysts (SACs) with a controllable coordination environment and exceptional atom utilization efficiency open new paradigms towards designing high performance water oxidation catalysts. Here, using<i> operando</i> X-ray absorption spectroscopy measurements with calculations of spectra and electrochemical activity, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Figure S8A-C, Supporting Information, indicate that both the specific activities and mass activities first increase with the decrease of Ni/Ir atomic ratios, but declines at a lower Ni/Ir ratio of 100/35, probably for the formation of Ir clusters in the FeNiP nanoparticles. [14] Particularly, for the Ir 25 -Fe 16 Ni 100 P 64 nanoparticles, the mass-based current density reaches 1.86 A mg −1 at 1.5 V versus RHE, suggesting their exceptional activity for OER in alkaline electrolyte. The high performance of the Ir 25 -Fe 16 Ni 100 P 64 nanoparticles for OER is also supported by their smaller Tafel slope and lower charge transfer resistance, as implied by Figure S8D,E, Supporting Information.…”
Section: Electrocatalytic Performance Toward Oer Under Alkaline Condi...mentioning
confidence: 94%
See 1 more Smart Citation
“…Figure S8A-C, Supporting Information, indicate that both the specific activities and mass activities first increase with the decrease of Ni/Ir atomic ratios, but declines at a lower Ni/Ir ratio of 100/35, probably for the formation of Ir clusters in the FeNiP nanoparticles. [14] Particularly, for the Ir 25 -Fe 16 Ni 100 P 64 nanoparticles, the mass-based current density reaches 1.86 A mg −1 at 1.5 V versus RHE, suggesting their exceptional activity for OER in alkaline electrolyte. The high performance of the Ir 25 -Fe 16 Ni 100 P 64 nanoparticles for OER is also supported by their smaller Tafel slope and lower charge transfer resistance, as implied by Figure S8D,E, Supporting Information.…”
Section: Electrocatalytic Performance Toward Oer Under Alkaline Condi...mentioning
confidence: 94%
“…[13] Especially, when Ir atoms replace some Ni atoms on the surface of NiFe oxyhydroxide catalyst, their valence state approaches to that of Ir in IrO 2 . [14] The high-valence single Ir atoms are believed to be beneficial for improving OER performance. [4b,15] In this context, we hypothesize that doping high-valence Ir single atoms into FeNi phosphides might be an effective way to combine the active noble metals with the synergistic interaction in bimetal phosphides for achieving desirable OER process.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [378] Copyright 2020, United States National Academy of Sciences. g) Gibbs free energy diagram of individual reaction steps involved in the OER process for Ir@Co nanosheets and Ir/C.…”
Section: Iridium-based Sacsmentioning
confidence: 99%
“…High OER activity of an Ir-based SAC was also reported by Zheng and co-workers. [378] Using DFT, the group developed several models for Ir doping into NiFe oxyhydroxide. However, only two models were identified with the substantial negative free energy of Ir doping.…”
Section: Iridium-based Sacsmentioning
confidence: 99%
“…[22][23][24] However, signicantly increased surface free energy with downsizing particles leads to the severe segregation of metal atoms in fabrication and employment processes, which is the culprit of low loading and instability of SACs. 25,26 Regarding this issue, some researchers found that appropriate supports with diverse anchoring and adsorption sites can prevent the sintering of single atoms (SAs) efficiently (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%